FoMO: Kecemasan Digital di Kalangan Pengguna TikTok - Darmayanti, Dyan Paramitha; Arifin, Iqbal; Inayah, Muh (Emik, 2023)
TikTok is one of the most popular social media today and has even become one of the social media that triggered the emergence of fear of missing out (FoMO) phenomenon. FoMO is a feeling of anxiety, discomfort, and restlessness felt by a person when he/she feels missing out on opportunities, experiences, or even interesting events presented by other TikTok users. While the existing literatures mostly focuse on the psychological aspects of FoMO and the reasons behind its occurrence, a novel contribution of this article is the different levels of FoMO experienced by those who experience it. Using a qualitative approach, this study was conducted between May 2023 and August 2023. There were ten participants involved in this study who had experienced or were currently experiencing FoMO. They varied in terms of gender (four males and six females) and age (between 18 and 24 years old), status (six university students, two employees and the other two high school students. Data were collected using in-depth interview and observation. The research shows that FoMO is the fear of something happening and going viral on TikTok, but when someone misses it or experience it, then he/she will feel left behind, which is popularly termed as "not updated". TikTok is very significant in causing FoMO because it contains unlimited content, is presented in a short duration, is easily accessed, so it can stimulate its users to always scroll (up, down, left, right), and poison its users. When they can't control themselves, they become addicted. There are four main levels of FoMO on TikTok: first, mild FoMO which is just a curiosity to participate in viral content; second, moderate FoMO, where users feel anxious about not being able to follow viral content and create a greater desire to engage; third, severe FoMO which can make users feeling stress and trying to always be connected to TikTok, even to the point of interfering with their daily activities; and finally, extreme FoMO which is the most dangerous level of FoMO because they feel trap by excessive FoMO, even to the point of wanting to end their lives. It is argued in this article that what level a person is at depends on how a person controls him/herself over the use of TikTok. Therefore, TikTok users must be careful from the beginning to control themselves, so that this super strong social media does not dominate its users